Novel Molecular Triggers of T-cell Activation and Fibrosis in Cardiac Stress and Cancer - Bayer, Abraham. (Tufts University. Tisch Library., 2025)
Thesis (Ph.D.)--Tufts University, 2025-05.; Submitted to the Dept. of Immunology.; Advisor: Pilar Alcaide.; Committee: Philip Hinds, Cheryl London, and Iris Jaffe.; Keywords: Immunology, and Medicine.